Web-Based Internship Scheduling System for Imelda Medan Vocational High School of Tourism Students Using the Ant Colony Optimization (ACO) Method - Suci Damai Gea; Barany Fachri; Hanna Willa Dhany (Bahasa Indonesia, 2026)
Field Work Practice (PKL) is an important component of vocational education that provides students with real workplace experience. However, scheduling PKL activities often encounters problems such as overlapping schedules, mismatched student quotas, and inefficient time management. At Imelda Medan Vocational High School of Tourism, the scheduling process is still done manually, which often leads to errors and delays. This study proposes a web-based PKL scheduling system using the Ant Colony Optimization (ACO) method to generate optimal and efficient schedules. The ACO algorithm imitates the behavior of ants in finding the shortest path, making it suitable for solving complex scheduling problems. The system is expected to minimize schedule conflicts, balance student placement, and simplify data management for schools, students, and partner industries.